2018
DOI: 10.1186/s12889-018-5407-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving social accountability processes in the health sector in sub-Saharan Africa: a systematic review

Abstract: BackgroundSocial accountability is a participatory process in which citizens are engaged to hold politicians, policy makers and public officials accountable for the services that they provide. In the Fifteenth Ordinary Session of the Assembly of the African Union, African leaders recognized the need for strong, decentralized health programs with linkages to civil society and private sector entities, full community participation in program design and implementation, and adaptive approaches to local political, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
(92 reference statements)
1
43
0
1
Order By: Relevance
“…Social accountability means building answerability through the engagement and direct or indirect participation of citizens/the public. To work effectively, accountability requires openness, dialogue, enforceability (ensuring an action is taken and consequences or remedies for a failure to do so) and honesty and responsiveness on the part of politicians, policy-makers, and providers to explain and justify their actions) (16). As Krubiner and Lakin (17) note, there is 'growing pressure [
] to create meaningful opportunities for public participation and deliberation [
] In some cases, this means inviting public participation for the first time on issues that were formerly decided in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…Social accountability means building answerability through the engagement and direct or indirect participation of citizens/the public. To work effectively, accountability requires openness, dialogue, enforceability (ensuring an action is taken and consequences or remedies for a failure to do so) and honesty and responsiveness on the part of politicians, policy-makers, and providers to explain and justify their actions) (16). As Krubiner and Lakin (17) note, there is 'growing pressure [
] to create meaningful opportunities for public participation and deliberation [
] In some cases, this means inviting public participation for the first time on issues that were formerly decided in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…There are several well-conducted reviews of community engagement, mobilisation, and participation, as well as human rights-based approaches to RMNCAH, which have significant overlap with accountability approaches [43][44][45][46][60][61][62]. Similarly, findings on accountability initiatives from outside the RMNCAH field can enhance our understanding of effective approaches that could be applied to RMNCAH [23,[29][30][31]33,36,[63][64][65][66][67][68]. In particular, lessons could be drawn on the conceptualisation and measurement of "empowerment," which though often listed as an individual or collective outcome of social accountability approaches, appears to be infrequently operationalized, and poorly described in existing research [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review reported a lack of institutional support, data and resources required for community and citizen empowerment and for participatory and deliberative approaches in health policy-making processes in sub-Saharan Africa. 48 Despite the existence of participatory health councils in 99% (1972/2000) of all Brazilian cities, there still exists a lack of full citizen and community empowerment in health policy decision-making. 49 , 50…”
Section: Limitationsmentioning
confidence: 99%